Fetal Therapies and Maternal-Fetal Tolerance - Tippi MacKenzie (Frontiers Research Topics, 2016)
The ability to diagnose and treat genetic diseases before birth represents one of the foremost breakthroughs of modern medicine. While fetal surgery has advanced in the last several decades, the prospect of applying developments in stem cell biology and gene therapy to the fetal environment remains an open frontier. This issue represents the work of international experts in the field of fetal therapy, who came together at the first meeting of the International Fetal Transplantation and Immunology Society in 2014. This meeting was convened in an effort to provide a consensus for future applications of in utero transplantation and gene therapy, as well as form an international community of colleagues to nurture this field.